Boycott of Pro-Zionist Products: A Contemporary Interpretation Study - Zulkarnain Muhammad Ali; Nisrina Nasution (Sekolah Tinggi Ilmu Ushuluddin (STIU) Darul Hikmah, 2025)
The Palestinian-Israeli conflict has been going on for more than seven decades and has become one of the most complex humanitarian issues in the modern world. Military invasions, land seizures, economic blockades, and human rights violations committed by Israel have sparked global reactions. One form of international response is the Boycott, Divestment, and Sanctions (BDS) movement. This study aims to analyze the theological legitimacy of boycotting pro-Zionist products through the perspective of contemporary interpretation of QS. At-Taubah verse 23. The research method used is qualitative based on literature study, with primary sources in the form of the Qur'an and Hadith, as well as secondary sources in the form of contemporary tafsir books such as Tafsir al-Maraghi, Fi Zhilalil Qur'an, Tafsir al-Azhar, Tafsir al-Munir, and Tafsir an-Nur. The results of the study show that QS. At-Taubah verse 23 affirms the principles of wala' (loyalty to Allah and the believers) and bara' (disassociating oneself from those who oppose Islam) and provides a strong basis for Muslims not to support those who oppose Islam, including through the consumption of products. The exegesis scholars agree that faith must be the main basis for determining attitudes, including in terms of shopping and economic support. Boycotts are a tangible form of faith, as well as a way of maintaining solidarity and strength among the ummah. In fact, boycotts have also been proven to weaken companies involved in supporting colonialism, as some of them have experienced a decline in profits due to global boycotts.